2022
DOI: 10.3389/fpubh.2022.917119
|View full text |Cite
|
Sign up to set email alerts
|

Spending and Hospital Stay for Melanoma in Hunan, China

Abstract: ObjectiveThis study aimed to describe the economic burden of Chinese patients with melanoma in Hunan province of China, and to investigate the factors for hospitalization spending and length of stay (LOS) in patients undergoing melanoma surgery.MethodsData was extracted from the Chinese National Health Statistics Network Reporting System database in Hunan province during 2017–2019. Population and individual statistics were presented, and nonparametric tests and quantile regression were used to analyze the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…All skin diseases were classified according to ICD-10 codes, defining 11 categories of skin diseases, and those not included were classified as "other skin diseases" (Supporting Information: Table S1). Based on a previous report, 8 hospital costs were adjusted by the 2018-2022 Hunan Consumer Price Index of medical care, which was derived from the annual report of the Hunan Provincial Bureau of Statistics (Supporting Information: Table S2).…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 99%
“…All skin diseases were classified according to ICD-10 codes, defining 11 categories of skin diseases, and those not included were classified as "other skin diseases" (Supporting Information: Table S1). Based on a previous report, 8 hospital costs were adjusted by the 2018-2022 Hunan Consumer Price Index of medical care, which was derived from the annual report of the Hunan Provincial Bureau of Statistics (Supporting Information: Table S2).…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 99%
“…4,7 Various studies have indicated that hospitalization expenditures may be influenced by factors such as healthcare insurance systems, length of hospital stay, and hospital classification. 7,8,9 While several investigations have explored the duration of stay and hospitalization expenses, the majority of attention has been directed toward major cancer types such as lung, breast, and colorectal cancer. 7,10,11 Few studies have described the characteristics of hospitalization costs for all types of cancer.…”
Section: Introductionmentioning
confidence: 99%